2019
DOI: 10.1158/1538-7445.sabcs18-p2-13-01
|View full text |Cite
|
Sign up to set email alerts
|

Abstract P2-13-01: Efficacy of neratinib in hormone receptor-positive patients who initiated treatment within 1 year of completing trastuzumab-based adjuvant therapy in HER2+ early-stage breast cancer: Subgroup analyses from the phase III ExteNET trial

Abstract: Background: The international, randomized, placebo-controlled phase III ExteNET trial showed that 1 year (yr) of neratinib 240 mg/day after trastuzumab-based adjuvant therapy significantly improved invasive disease-free survival (iDFS) in 2840 patients with early-stage HER2+ breast cancer at 2 yr (hazard ratio 0.67; 95% CI 0.50–0.91; p=0.009) [Chan 2016] and 5 yr (hazard ratio 0.73; 95% CI 0.57-0.92; p=0.008) [Martin 2017]. A prespecified subgroup analysis by hormone receptor (HR) status suggested enhanced eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Interestingly, the subgroup of patients with residual invasive disease after NAC showed clinically meaningful improvements in DFS and OS, but these results should be interpreted with caution due to the exploratory nature of the analysis and the small number of patients [ 32 ].…”
Section: Her2-positive Breast Cancermentioning
confidence: 99%
“…Interestingly, the subgroup of patients with residual invasive disease after NAC showed clinically meaningful improvements in DFS and OS, but these results should be interpreted with caution due to the exploratory nature of the analysis and the small number of patients [ 32 ].…”
Section: Her2-positive Breast Cancermentioning
confidence: 99%
“…In the recent data from subgroup analyses from the phase III ExteNET trial has shown that Neratinib may have enhanced and sustained efficacy in patients with HR+ disease who initiate treatment within 1 yr of trastuzumabbased adjuvant therapy. 25…”
Section: Neratinibmentioning
confidence: 99%